Micronutrient Deficiency and Autophagy Dysregulation in Pulmonary Tuberculosis Pathogenesis: A Systematic Review - Salma Winda Aufa; Delmi Sulastri (Al-Hijrah Indonesia, 2026)
Pulmonary tuberculosis remains a critical global health burden, with Indonesia ranking second in the world for the highest TB burden. Autophagy is an essential innate immune mechanism for eliminating intracellular Mycobacterium tuberculosis (Mtb) in macrophages, but it is susceptible to dysregulation by micronutrient deficiencies, which are highly prevalent in populations with active TB. This systematic review aims to synthesize scientific evidence on the effects of deficiencies in vitamin D, vitamin A, zinc, and selenium on the dysregulation of the autophagy pathway and its implications for the pathogenesis of pulmonary tuberculosis. Literature searches were performed in PubMed and ScienceDirect for studies published from 2006 to 2025, using a combination of MeSH terms and free-text keywords. A total of 11 studies were included in the final synthesis. The results of the synthesis indicate that vitamin D deficiency inhibits the transcription of autophagy genes (LC3, Beclin-1, ATG5) by disrupting VDR signaling. Combined zinc and vitamin D deficiency reduces autophagy capacity by up to 85% and correlates with worse clinical outcomes of TB. Specifically, zinc and vitamin D deficiencies act synergistically to inhibit autophagy, representing the most significant interaction. Micronutrient deficiencies were shown to dysregulate autophagy through distinct yet synergistic molecular pathways, facilitating Mtb persistence and exacerbating the pathogenesis of pulmonary TB. Micronutrient supplementation holds potential as an adjuvant host-directed therapy strategy in the management of pulmonary tuberculosis.